OPTIMIZING INCLUSIVE PHYSICAL EDUCATION THROUGH PEER TUTORS TO IMPROVE STUDENTS’ NON-LOCOMOTOR SKILLS AND SELF-CONFIDENCE - Almiansyah Almiansyah; Erwin Setyo Kriswanto; Lantip Diat Prasojo; Eka Sapti Cahya Ningrum; Shely Cathrin (PT Altin Riset Publishing, 2026)
This study aims to analyze the application of the peer-tutoring method in inclusive Physical Education, Sports, and Health (PJOK) instruction to improve the basic non-locomotor motor skills and self-confidence of slow learners. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The study was conducted in two cycles during the even semester of the 2025/2026 academic year at SD Negeri 002 Sangkulirang, East Kutai Regency. The research subject was a fourth-grade student with the initials AL who was identified as a slow learner. Data were collected through observation, semi-structured interviews, field notes, and documentation, then analyzed descriptively by integrating quantitative and qualitative data. The results showed an increase in non-locomotor basic motor skills from 46% in the pre-cycle to 71% in Cycle I and 83–85% in Cycle II. Self-confidence also increased from 35% in the pre-cycle to 75% in Cycle I and 85% in Cycle II. These improvements were accompanied by behavioral changes, including the courage to try, the ability to follow instructions, the courage to ask questions, a willingness to perform in front of the class, group participation, and independence in performing movements. The findings indicate that peer tutoring has the potential to serve as an inclusive pedagogical strategy that integrates scaffolding, social support, experiences of success, and repeated practice to strengthen both the motor skills and psychosocial aspects of students with learning difficulties. Although the results are limited to a single subject, the study offers practical implications for the development of adaptive and participatory Physical Education (PJOK) programs.